Sleep quality of adult recreational cannabis users: a systematic literature review - Nathália Lima Costa; Wennyo Camilo da Silva e Silva; Marianne Lucena da Silva; Katiane da Costa Cunha (Trends in Psychiatry and Psychotherapy)
Abstract Objective: Human sleep is fundamental for the proper occurrence of organic functions. Hence, lack of sleep can impair cognitive function, resulting in emotional problems, memory changes, and disease onset. However, it is worth noting that sleep is influenced by outside factors, such as drug use. In this sense, the aim of this review is to analyze studies that researched the influence of recreational marijuana on the sleep quality of adults. Methods: High-sensitivity searches were conducted on databases (Biblioteca Virtual em Saúde [BVS], MEDLINE via PubMed, Cochrane, Embase, Web of Science, and Scopus) using descriptors related to marijuana and sleep habits. Results: Eighteen studies from four countries were included with a total sample size of 29,858 participants. It was found that marijuana affects sleep characteristics – such as latency and duration – with these changes being more evident in users who make greater use of marijuana and in those with early onset of marijuana use. Conclusion: It was observed that most articles demonstrated a detrimental effect of recreational cannabis use on the quality of sleep in adults.